2010
DOI: 10.3109/13682820903560302
|View full text |Cite
|
Sign up to set email alerts
|

Indirect language therapy for children with persistent language impairment in mainstream primary schools: outcomes from a cohort intervention

Abstract: At present, the more efficacious therapy is that delivered by speech and language therapists or speech and language therapy assistants to children individually or in groups. This may be related to more faithful adherence to the interventions schedule, and to a probably greater amount of language-learning activity undertaken. Intervention delivered via school-based 'consultancy' approaches in schools will require to be carefully monitored by schools and SLT services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 16 publications
2
51
0
1
Order By: Relevance
“…Expressive language gains were reported in the first two, but not the latter study. In the case of the consultancy approach (McCartney et al, 2011), mainstream staff failed to implement the amount of language-learning activity required to adhere to the therapeutic program possibly because the staff simply did not have sufficient resources to manage the added demands of providing the intervention program. Indeed, there is evidence that SLP consultation may not necessarily lead to changed teacher behaviour (Noell & Witt, 1999), that teachers may not report benefiting from SLP consultations (Dockrell & Lindsay, 2001), and may have little access to SLPs for consultation (Baxter, Brookes, Bianchi, Rashid, & Hay, 2009).…”
Section: The Challenge Of Changementioning
confidence: 99%
See 1 more Smart Citation
“…Expressive language gains were reported in the first two, but not the latter study. In the case of the consultancy approach (McCartney et al, 2011), mainstream staff failed to implement the amount of language-learning activity required to adhere to the therapeutic program possibly because the staff simply did not have sufficient resources to manage the added demands of providing the intervention program. Indeed, there is evidence that SLP consultation may not necessarily lead to changed teacher behaviour (Noell & Witt, 1999), that teachers may not report benefiting from SLP consultations (Dockrell & Lindsay, 2001), and may have little access to SLPs for consultation (Baxter, Brookes, Bianchi, Rashid, & Hay, 2009).…”
Section: The Challenge Of Changementioning
confidence: 99%
“…Another concern arises regarding identifying someone available to work with a child in the classroom who has the necessary knowledge and skills to implement programming suggestions from the SLP (Law, Lindsay, Peacey, Gascoigne, Soloff, Radford, & Band, 2002). A potential example of such constraints comes from a series of studies by Boyle and McCartney and colleagues reporting a manualized language therapy program for primary school children with DLD delivered to small groups by SLPs (Boyle, McCartney, Forbes, & O'Hare, 2007), speech and language assistants (Boyle, McCartney, O'Hare, & Forbes, 2008), or by mainstream school staff through consultation with the SLPs (McCartney, Boyle, Ellis, Bannatyne, & Turnbull, 2011). Expressive language gains were reported in the first two, but not the latter study.…”
Section: The Challenge Of Changementioning
confidence: 99%
“…However, a follow-up study (McCartney et al, 2011), using the same intervention but delivered by school staff (teachers, deputy head teachers, language support teachers and classroom assistants), found no effect of intervention for either receptive or expressive language relative to the Boyle et al (2009) historical controls. The most likely reason for this is probably the limited amount of intervention actually delivered.…”
Section: Language Intervention Packagesmentioning
confidence: 99%
“…The major difference between the Boyle et al (2007;McCartney et al (2011) studies was in the background and employment those delivering the intervention. In Boyle et al (2007;, they were employed by the researchers running the study and were psychology graduates.…”
Section: Language Intervention Packagesmentioning
confidence: 99%
“…The studies at Tier 3A demonstrating good outcomes for children had high levels of support for parents (Tosh et al, in press), or professionals who were employed and supervised directly by the SLT service or research team (Boyle et al, 2009;Mecrow et al, 2010). In the only study where the level of support provided to staff carrying out intervention resembles that provided by current routine SLT services (at least in the UK, McCartney et al, 2011), the intervention did not take place as planned and the children showed no progress. This highlights the need for regular monitoring and support in order to ensure that indirect intervention takes place as intended.…”
Section: Training For Parents or Education Staffmentioning
confidence: 99%